Conocimiento y prácticas preventivas de parasitosis intestinal en madres con niños de 2 a 5 años del asentamiento humano Nuevo Canaán Iquitos 2024 - Pinedo Alvarado, Ines Natali (2024)
The purpose of the study was to determine the relationship between knowledge and preventive practices of intestinal parasitosis in 75 mothers with children aged 2 to 5 years, from A.H. New Canaan; quantitative, non- experimental, descriptive, cross-sectional and correlational. The techniques were the survey and home visit; and the instruments were a knowledge questionnaire (validity 85.83% and reliability 84.33%) and a questionnaire on preventive practices of intestinal parasitosis (validity 92.50% and reliability 81.3%). The results were: 40.0% (30) of mothers presented medium knowledge, 34.7% (26) low and 25.3% (19) high. Regarding preventive practices, 61.3% (46) were inadequate and 38.7% (29) adequate. Significance was found between knowledge and preventive practices of intestinal parasitosis (X2c = 7.521; Gl = 2; p = 0.023 < 0.05). Concluding that mothers with average knowledge showed inadequate preventive practices of intestinal parasitosis; requiring immediate educational intervention, to reduce this great public health problem.